2021
DOI: 10.20961/jphystheor-appl.v5i2.59133
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Earthquake Activity in Indonesia by Clustering Method

Abstract: Indonesia is an area where three large tectonic plates meet, namely the Indo-Australian, Eurasian and Pacific plates, so that Indonesia is included in the earthquake-prone category, with 11,660 earthquake vibrations identified in the Meteorology, Climatology and Geophysics Agency (BMKG) database in 2019 The purpose of this study is to develop a classification of the distribution of earthquakes in Indonesia in 2019 based on the values of magnitude, depth, and position. This research was conducted by using the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
2
10
0
1
Order By: Relevance
“…Schools have a central role in developing disaster preparedness in the school environment, especially on the island of Flores. This is in accordance with research (Handayani, 2020;Jufriansah et al, 2021), which revealed that the geological setting of Flores Island is part of the Pacific Ring of Fire. This finding reinforces the tsunami events disclosed by Pranantyo et al (2021) and Pranantyo & Cummins (2019).…”
Section: B Discussionsupporting
confidence: 92%
“…Schools have a central role in developing disaster preparedness in the school environment, especially on the island of Flores. This is in accordance with research (Handayani, 2020;Jufriansah et al, 2021), which revealed that the geological setting of Flores Island is part of the Pacific Ring of Fire. This finding reinforces the tsunami events disclosed by Pranantyo et al (2021) and Pranantyo & Cummins (2019).…”
Section: B Discussionsupporting
confidence: 92%
“…To avoid missing data, the data cleaning procedure is then performed [20], [21]. By focusing on the least squares alternative or optimizing the probability function, this method employs imputation [22]. Fig.…”
Section: Resultsand Discussionmentioning
confidence: 99%
“…The triggers that most often occur are caused by mountain and sea activities resulting in frequent movements of the earth's slopes resulting in vibrations so that the risk is fatal which can result in fatalities and environmental damage [1]- [3]. Several cases that often occur due to fatalities, namely the unconsciousness of the occupants of the house due to an earthquake such as being at work, falling asleep and also not having an alarm at home so that the owner of the house is complacent so he cannot run out of the house [4]- [7]. North Sumatra is an area where earthquakes frequently occur due to Mount Sinabung [8], [9].…”
Section: Introductionmentioning
confidence: 99%